Factors affecting the shadow economy and their impact on economic growth in the Kingdom of Saudi Arabia during the period (2007-2021) - Nasrulddin, Vivian Mohammed Saleh; Alshahrani, Hessa Saad (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the factors affecting the shadow economy and their impact on economic growth in the Kingdom of Saudi Arabia, during the period (2007-2021). A multiple linear regression analysis model has been described to express the relationship between the shadow economy in the Kingdom as a dependent variable, and the independent variables associated with the shadow economy. Which were selected based on previous studies and researchers' jurisprudence, which are represented in: the number of foreign workers, the volume of oil exports, the unemployment rate, the inflation rate, the Saudization rate, the total number of commercial records. By identifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified, by the statistical program E-views(9). As expected, the results showed a significant positive relationship between the dependent variable and both the total number of foreign workers and the unemployment rate. While the study showed - contrary to what was expected - that the rest of the independent variables did not affect the size of the hidden economy in the Kingdom during the study period.
Keywords: Hidden economy; Money laundering; Commercial cover-up; Legitimate activities; Illegal activities; Black market